Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-60624-z
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism of the equine cumulus oocyte complex during in vitro maturation

Abstract: Horses are one of the few species, beside humans, in which assisted reproductive technology has important clinical applications. Furthermore, the horse can serve as a valuable model for the study of comparative reproductive biology. Here we present the first comprehensive characterisation of energy metabolism and mitochondrial efficiency in equine cumulus-oocyte complexes (COCs) during in vitro maturation (IVM), as determined using a combination of non-invasive consumption and release assays and mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 59 publications
3
31
0
1
Order By: Relevance
“…Regarding pyruvate, this molecule has been previously reported to range between 0.03 and 0.13 mM in FF from early and late dominant equine follicles, respectively [19]. This metabolite has been demonstrated to be crucial for adequate oocyte metabolism [5] and is also involved in active reactive oxygen species scavenging [20]. In equine oocytes, it has been demonstrated that when DMEM/F-12 is supplemented with pyruvate at 0.15 mM, this induces an increase in glycolytic activity, without affecting mitochondrial oxidative phosphorylation [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding pyruvate, this molecule has been previously reported to range between 0.03 and 0.13 mM in FF from early and late dominant equine follicles, respectively [19]. This metabolite has been demonstrated to be crucial for adequate oocyte metabolism [5] and is also involved in active reactive oxygen species scavenging [20]. In equine oocytes, it has been demonstrated that when DMEM/F-12 is supplemented with pyruvate at 0.15 mM, this induces an increase in glycolytic activity, without affecting mitochondrial oxidative phosphorylation [5].…”
Section: Discussionmentioning
confidence: 99%
“…This metabolite has been demonstrated to be crucial for adequate oocyte metabolism [5] and is also involved in active reactive oxygen species scavenging [20]. In equine oocytes, it has been demonstrated that when DMEM/F-12 is supplemented with pyruvate at 0.15 mM, this induces an increase in glycolytic activity, without affecting mitochondrial oxidative phosphorylation [5]. The concentration of pyruvate above reported for equine FF [19] coincides with our work in which 0.16 mM ± 0.03 was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, lactate dehydrogenase B (LADHB) is involved in lactate synthesis from pyruvate, and it is known that lactate is a core metabolite found in equine OF (11). Lactate is required to maximize mitochondrial activity and motility in equine spermatozoa incubated under capacitating conditions (37) and is also required during in vitro oocyte maturation (38,39). Hence, the downregulation of LADHB in post-ovulatory OF compared to pre-ovulatory OF could also be related to the specific lactate needs of equine gametes during capacitation and fertilization.…”
Section: Discussionmentioning
confidence: 99%